DESCRIPTIVE TEXT WRITING OF STUDENTS WITH NATURAL AND SOCIAL SCIENCE MAJORS - Miftahul Mar'ie Susetio; Berlin Sibarani (Universitas Negeri Medan, 2021)
This study aimed at identifying how the students of natural and social science majors write descriptive text writing based on the usage of process. This study was conducted by applying descriptive qualitative method. The sources of data were taken from natural and social science students’ descriptive text writing. The results of this research showed that the natural science and social science students used types of process differently in writing their descriptive text. The students from natural science used relational process as the dominant type of process in their description. From 150 types of process used in 13 texts, they use 104 relational processes, it’s 69.33%. They tend to use verbs such as ‘be/is/am/are as attributes and identifications, they also tend to use ‘have/has’ which refers to possession. On the other hand, the dominant type of process used in social science students’ descriptive text writing is existential process. From 107 types of process used in 13 texts, 50 (46.7%) of them are existential process. The findings of the study also showed that the different use of types of process from natural and social science students affected their way in describing object and their way in writing descriptive texts.Keywords: Descriptive, Writing, Process, Natral Science, Social Science